PENERAPAN PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL PjBL UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN 09 PONTIANAK BARAT - Agustina Silitonga; Bharat Dewangga; Elma Tiana; Rohis Tegar (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
This classroom action research aims to improve the science learning outcomes of fifth-grade students at SD Negeri 09 Pontianak Barat. This study implemented a project-based differentiated learning (PjBL) approach, tailored to students' needs and characteristics. The background of this study stems from low pre-cycle learning outcomes, with a class average of 56.30 and only 29.63% of students achieving the Minimum Passing Score (KKM = 65). This study uses the Classroom Action Research (PTK) method, conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The research subjects were 27 fifth-grade students. Data collection techniques included tests, observations, and documentation. The results showed significant improvement: in Cycle I, the class average increased to 70.56 with a class mastery rate of 62.96%; in Cycle II, the class average reached 82.59 with a class mastery rate of 88.89%, exceeding the 80% success indicator. This study concludes that differentiated instruction through the PjBL model, implemented through differentiation of content, process, and product, is effective in improving students' IPAS learning outcomes. Keywords: Differentiated Instruction, Project-Based Learning, IPAS Learning Outcomes, Elementary School.